Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae) - Kirchner, Sandra; Kruckenhauser, Luise; Pichler, Arthur; Borkenhagen, Kai; Freyhof, Jörg (Zootaxa, 2020)
The Garra species inhabiting the Hajar Mountains are revised and five species are recognised, two of which are newly species described herein. Garra barreimiae, from the United Arab Emirates (UAE) and Northern Oman, is distinguished from other Garra species in the Hajar Mountains by a strongly mottled flank pattern with individual or series of midlateral orange scales, a white dorsal-fin tip, an orange spot at the upper operculum, and more gill rakers on the lower limb of the first gill arch. Garra barreimiae shawkahensis is a synonym of G. barreimiae. Garra gallagheri, from the Wadi Bani Khalid drainage in Oman, is distinguished by flank-scale margins the same colour or slightly darker than the centre of the scales. Garra longipinnis, from the interior wadis in the Central Hajar Mountains in Oman, is distinguished by flank-scale margins being clearly darker than the centre of scales. The original description of G. longipinnis was based on a few individuals with very large fins, which are here considered aberrant. Garra shamal, new species, from the coastal drainages around Muscat in Oman, is distinguished by a strongly mottled flank pattern usually without orange midlateral scales, a white dorsal-fin tip, no orange spot at the upper operculum, and middle caudal-fin rays and membranes the same colour or slightly darker than the rest of the fins in colouration. Garra sharq, new species, from the Wadi Kabbah drainage and a few interior springs in Oman, is distinguished by a strongly mottled flank pattern with individual or series of orange midlateral scales, no orange spot at the upper opercle, and dorsal-fin tip and membranes between central caudal-fin rays the same colour as the rest of the fins. All five species are well differentiated genetically and form distinct mitochondrial clades with between 2.1 and 9.2% differences (p-distances) in the mitochondrial COI.